Assessing self-reported empathic tendencies of teachers and psychology students - Almeda-Estanislao, Susan R. (2006)
This study identified the emphatic behavioral modes of teachers and psychology students across different locations/cultures. It served a two-fold purpose: (1) to examine if different groups significantly differ in their manner of expressing emphatic tendencies considering their location / culture; and (2) to explore the major issues and concerns of students as reported by them and as perceived by the teachers. In order to address these research goals, the quantititative and qualitative approaches were employed. A total number of 196 teachers and students served as participants. Survey method was used to gather research data. Results reveal that the teachers from Manila expressed empathy by responding verbally when compared with teachers coming from the outskirts of Manila and from the provinces and to psychology students from various locations / cultures.
Keywords: Empathy -- Testing; Teacher attitudes -- Research; College student attitudes